A new 3D-printed photoelectrocatalytic reactor combining the benefits of a transparent electrode and the Fenton reaction for advanced wastewater treatment. Issue 47 (23rd November 2017) - Mousset, Emmanuel; Huang Weiqi, Victor; Foong Yang Kai, Brandon; Koh, Jun Shyang; Tng, Jun Wei; Wang, Zuxin; Lefebvre, Olivier
Abstract : A new TiO2 -coated stirred glass reactor was designed, comprising a film of fluorine-doped tin oxide (FTO) coated on a transparent glass anode. Abstract : A new TiO2 -coated stirred glass reactor was designed, comprising a film of fluorine-doped tin oxide (FTO) coated on a transparent glass anode. The potential of FTO for the O2 evolution reaction – determined by linear scan voltammetry – was equal to 2.1 V vs. the SHE, high enough to form hydroxyl radicals (˙OH) through anodic oxidation (AO). By letting UVA light shine through the glass reactor coated with an optimal TiO2 loading of 0.311 mg cm −2, heterogeneous photocatalysis occurred, which led to a second source of ˙OH. Coupled with a three-dimensional (3D) carbonaceous cathode and with the addition of a catalytic amount of Fe 2+, four more sources of ˙OH could be implemented through H2 O2 electro-activation, the Fenton reaction, H2 O2 photolysis and Fe(iii )-hydroxy complex photolysis. This combined photoelectrocatalytic Fenton process allowed reaching a phenol (chosen as a model pollutant to allow for easy comparison with other processes) degradation rate of 0.0168 min −1 and a mineralization yield of 97% after 8 h of treatment, far better than those of each individual process. Notably, the phenol degradation rate of the combined process was 37% higher than that of electro-Fenton (EF) alone and 42% higher than that of AO alone. A synergy was observed (with a photocatalytic synergy value of S PC = 1.26) in the presence of TiO2, which improved on UV photolysis alone (UV synergy value, S UV = 0.97) and could be further augmented in a novel 3D-printed flow-cell reactor, designed to maximize the distance of electrode separation and the contact between gaseous O2 and the carbon cathode. Indeed, UVA radiation shining through the FTO anode – with a transmissivity of 65% – improved the kinetics of photolytic reactions as compared to dark processes, with a synergy value ( S UV ) as high as 1.87. Thanks to these enhancements, the overall phenol degradation rate could be further increased to 0.0175 min −1, 14% higher than that within the stirred glass reactor (0.0153 min −1 ). Following optimization of the current density and Fe 2+ concentration, a kinetic rate of degradation of 0.0214 min −1 was attained, an all-time high showcasing the promise of the novel photoelectrocatalytic reactor.